Beda Czcigodny o wczesnym chorale gregoriańskim w Anglii (Historia ecclesiastica IV 24) - Budzanowska-Weglenda, Dominika Łucja (Vox Patrum, 2019)
In the famous work Historia ecclesiastica in Book IV of Chapter 24 Bede the Venerable (672/3-735), an Anglo-Saxon monk and a Doctor of the Church, wrote about the religious brother named Cædmon. Earlier Cædmon avoided secular singing, when he worked as a keeper of draft animals, but God gave him the gift of singing for the glory of God. This man adapted to the monastery by the abbess Hilda arranged in his native language – under the influence of God-Creator inspiration and downloading theological sciences – pious songs connected with biblical events and various theological threads. In this way he encouraged people to convert and strengthen their faith. None of Cædmon’s followers matched him with talent. The notes of Bede may testify not only to strong monasticism at the very beginning of Anglo-Saxon Christianity, but also to care for religious songs, probably the beginning of Gregorian chant in England.